A General Characterization of Adaptive Logics - Batens, Diderik (Logique et Analyse, 2001)
This paper contains a unified characterization of adaptive logics. The general structure is presented in the simplest possible guise, both for flat and prioritized adaptive logics. The latter are presented as a special case of combined adaptive logics. The aim of the paper is to provide the general framework underlying several other papers in this volume and to prepare the unified metatheory of adaptive logics.
Appeared 2003